English ludic corner as a teaching resource for the learning process in students of fifth year“a” of basic education at “Mariscal Sucre School”, during the academic cycle 2012 – 2013 - Guanochanga Cuchipe, Carmen Beatriz (2014)
Learning English is very important for students of fifth year "A" of Basic Education at Mariscal Sucre School where this research was conducted to know the problem that teachers and students have. The children cannot express their ideas in a clear and concrete way because they don’t manage enough vocabulary and don’t have suitable teaching methods that encourage them to develop their English communication skills such as Listening, Speaking, Reading and Writing. In fact, teachers are limited to use traditional teaching resources such as photocopies and textbooks, becoming monotonous the English language learning for their students. In addition, teachers apply the same strategies and techniques for all class activities which don’t permit to develop the teaching-learning process in a dynamic and interesting form. That’s way the purpose of this research was to design the necessary and appropriate ludic materials, which help teachers motivate students in learning a foreign language such as English. These resources help students and teachers to maintain a good working environment in the classroom and make lessons interesting and meaningful, so children can improve their academic level and interact with their partners in a fun way. The guide contains a detailed explanation of each recreational activity like dynamic games, puzzles, hopscotch, etc. It also includes the respective description and instruction about materials and activities to facilitate the understanding. Finally, the contribution of this research was to motivate teachers and students to use ludic materials in English classes. The method used in this research work was the descriptive, and included a population of 65 people, which helped to obtain actual data for doing statistical analysis of each question of the survey. The education supported on ludic resources facilitates the interaction among teacher, student and didactic materials.